Development of water production function for French bean (Phaseolus vulgaris L.) under mid hills of Meghalaya - Mishra, Guru Prasad; Ray, Lala I. P. (Umiam : CPGS-AS, CAU(I), 2024)
In the realm of climate change, water scarcity poses a serious challenge towards agricultural food production. The crops grown in the Northeastern hilly region (NEHR) of India experience acute terminal moisture stress during rabi season due to insufficient rainfall coupled with high evaporative demand. In such water scarce situation, deficit irrigation is one of the water management strategies in which crops were irrigated with less amount of what required by the crop to meet the crop evapotranspiration (ET) demand without compromising the potential yield. Hence, it is essential to understand the response of crop yield to moisture stress for which water production functions are derived in order to allocate irrigation water efficiently for increasing water productivity. In light of the aforementioned considerations, an agronomic field experiment entitled (3z(BDevelopment of Water Production Function for French bean (Phaseolus vulgaris L.) under Mid Hills of Meghalaya(3y (Bwas carried out using a split plot design which included four level of available soil moisture depletion (ASMD) viz., M1 (20% of ASMD), M2 (40% of ASMD), M3 (60% of ASMD) and M4 (80% of ASMD) under main plot and three French bean varieties viz., Arka Arjun (V1), Arka Sharath (V2) and Zorin bean (V3) under sub plot treatment and replicated thrice. The experiment yielded the following results: Irrigation regime M1 exhibited significantly highest growth parameter such as plant height (73.43 cm), leaf area index (3.02), number of branches per plant (9.06), dry matter accumulation per plant (30.19 g), and maximum value of yield attribute viz., number of pods per plant (7.14), number of seeds per pod (4.10) and economic (seed) yield (1024 kg ha-1 ). However, irrigation regime M2, where crops were irrigated at 40% of ASMD was at par with irrigation regime M1. The irrigation regime M4 registered significantly maximum water productivity of 0.45 kg m-3 followed by M2 (0.39 kg m-3 ) M3 (0.31 kg m-3 ) and M1 (0.26 kg m-3 ). The response of crop yield to total amount of water was established through a quadratic water production; y = -0.0159x2 + 9.8331x - 467.28 (R2 = 0.96) on a pooled basis for all three varieties which fits well as compared to the linear one. Zorin bean outperformed other varieties in the subplot treatment, achieving the highest seed yield (1104 kg ha-1 ) and water productivity (0.47 kg m-3 ). Likewise, the maximum value of benefit cost ratio was obtained under main plot treatment M2 (1.94) and Zorin bean obtained a benefit cost ratio of 2.18 among the variety. Considering the field trial results, it's advisable to recommend irrigation at 40% of ASMD during rabi season in NEHR especially in Meghalaya. Although this deficit irrigation strategy may lead to a minimal yield reduction, it doesn't significantly affect the maximum potential yield, and it leads to higher water productivity compared to 20% of ASMD.s
Includes bibliographical references.
Keywords: French bean; Phaseolus vulgaris L